(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Parents’ support is the process of assisting, especially financially, to enable them to function or act. It is a way to encourage and approve someone or something because you want the person or thing to succeed. Parents’ support has a positive influence on our physical and mental health. It plays a vital role in improving student’s academic performance. The study used descriptive research design to formulate a hypothesis and to determine and describe the level of support of parents on the distance learning of Grade 12 HUMSS students towards academic performance. A simple random sampling method was used to select a participant who will serve as a respondent. Surveys and online questionnaires were used as research instruments for data collection. The primary purpose of this study is to examine the Level of support of parents on the distance learning of Grade 12 HUMSS students towards academic performance. Earlier research shows that parents faced issues supporting their children’s learning, such as a shortage of time. The results reveal that most parents have to work to maintain the family’s financial standing. In addition, they also experienced the problem of lack of internet access, lack of interest in using technology and having low digital self-efficacy. Undeniably, in some ways, the new normal education system affects parents’ level of support for the Grade 12 HUMSS student towards academic performance.